2013
DOI: 10.1200/jco.2012.46.1517
|View full text |Cite
|
Sign up to set email alerts
|

Hospital and Surgeon Volume in Relation to Survival After Esophageal Cancer Surgery in a Population-Based Study

Abstract: Because surgeon volume rather than hospital volume independently influences the prognosis after esophageal cancer surgery, centralization of this surgery to fewer surgeons seems warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
119
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 176 publications
(189 reference statements)
3
119
0
3
Order By: Relevance
“…These observations are in line with those of other studies involving oncologic surgery, in which long-term results significantly improved with greater surgeon experience. [24][25][26][27] Moreover, these results are consistent with the primary hypothesis of this study that, whereas the immediate and perhaps midterm outcomes are equally influenced by individual experiences of surgeons during hepatectomy and graft implantation, the long-term outcomes are affected mostly by the experiences of surgeons performing graft implantation. Interestingly, the positive effects of greater experience of the surgeon performing graft implantation were observed only for conventional and not for piggyback liver transplant procedures.…”
Section: Discussionsupporting
confidence: 89%
“…These observations are in line with those of other studies involving oncologic surgery, in which long-term results significantly improved with greater surgeon experience. [24][25][26][27] Moreover, these results are consistent with the primary hypothesis of this study that, whereas the immediate and perhaps midterm outcomes are equally influenced by individual experiences of surgeons during hepatectomy and graft implantation, the long-term outcomes are affected mostly by the experiences of surgeons performing graft implantation. Interestingly, the positive effects of greater experience of the surgeon performing graft implantation were observed only for conventional and not for piggyback liver transplant procedures.…”
Section: Discussionsupporting
confidence: 89%
“…A cohort study found that surgeon volume was a stronger prognostic factor than hospital volume after mutual adjustment. 90 Even experienced surgeons who start to perform oesophagectomies have a learning curve before the survival outcome for their patients is stabilised. 88 Taken together, available scientific evidence supports centralisation of oesophagectomy.…”
Section: Volumementioning
confidence: 99%
“…This comprehensive cohort has been presented in detail elsewhere [4]. Importantly, the study cohort included copies of the operation charts for esophageal cancer surgery from the medical records throughout Sweden during the period 1987-2010.…”
Section: Methodsmentioning
confidence: 99%
“…However, for many patients, overall survival (OS) remains limited [2,3]. Doses of at least 60 Gy in 2 Gy/fraction are frequently used [4] and clinically relevant acute radiation esophagitis (RE) is relatively common [5]. RE is found to correlate with different dose-volume parameters [6-10] and normal tissue complication probability (NTCP) models have been developed for RE [11,12].…”
Section: Letter To the Editormentioning
confidence: 99%